Environmentally Benign Approaches towards the Synthesis of Quinolines. Issue 22 (9th June 2022) - Kumar, Asim; Dhameliya, Tejas M.; Sharma, Kirti; Patel, Krupa A.; Hirani, Rajvi V.
Abstract: Greener and sustainable synthetic strategies have been evolving as the demanding domain of organic transformations during the last decade. The division of an environmentally benign methodology to construct bioactive heterocyclic scaffolds has always been a perpetual subject of interests for medicinal and synthetic chemists. Thus, the newer and novel synthetic methodologies of quinoline have drawn the attention of synthetic organic or medicinal chemists as evident from the growing numbers of publications. The current review focuses on some of the notable synthetic methodologies carried out in the last decade with the inherent objective to attain sustainability towards the synthesis. The key aspects of the review would include to highlight sustainable and environmentally benign approaches like the solvent‐free reactions, use of alternate reaction media (e. g., water, fluorous alcohols, polyethylene glycols, and ionic liquids), and alternate modes of synthesis such as microwave‐assisted synthesis and flow reactions, nano‐catalysts, etc. Abstract : Coverage of the green synthetic reports for the synthesis of quinolines have been discussed along with their classification of sustainable alternatives, merits and demerits of the reported synthetic protocols, and special emphasis on water, microwave, ionic liquids, photocatalysts, and nano‐catalysts assisted organic transformations.